Do religious values of prospective teachers affect their attitudes toward science teaching? - (:unkn) unknown (My University, 2009)
This study aimed to examine the associations between prospective science teachers' values (theoretical, religious, economic, aesthetic, social and political values) and their attitudes towards science teaching. Cross-sectional research design was used. Science Teaching Attitude Scale-II and Allport-Vernon-Lindzey Values Test were used for assessing prospective science teachers' attitudes toward science teaching and their values respectively. As a result of list-wise deletion, the sample appeared to be 281 prospective science teachers. Regression analysis showed that religious value of prospective science teachers was a significant predictor of their attitudes toward science teaching (F (1, 279) = 14.787, p<.01). In order to neutralize the possible negative impacts of religious values, it is suggested that science teachers must be aware that religion and science are two different ways of knowing. In this respect, the present study implies the importance of explicitly discussing different ways of knowing in science teacher training programmes.
Keywords: Attitudes toward science teaching; Prospective science teachers; Values